Telecommunication theory : Textbook. Part 2 - Ivaschenko, Petro V.; Іващенко, Петро Васильович; Іващенко, П. В.; Розенвассер, Денис Михайлович; Розенвассер, Д. М.; Rozenvasser, Denys M. (Odesa : O. S. Popov ONAT, 2017)
The Telecommunication Theory textbook consists of two parts: part 1 – «Communication Signals» and «Theory of Noise Immunity of Tele- communication Signals Reception»; part 2 – «Transmission of Information in Telecommunication Systems» and «Bases of the Error-control Codes Theory». This textbook (part 2) contains main theoretical positions, questions for check- ing the knowledge and English-Russian and Russian-English dictionaries of terms. The textbook is intended for students majoring in 172 – Telecommunications and radio technology studying the Telecommunication Theory.
Ivaschenko P. V. Telecommunication theory : textbook. part 2 / P. V. Ivaschenko, D. M. Rozenvasser. – Odesa : O. S. Popov ONAT. – 2017. – 110 p.
Keywords: Quantitative measure of the information; Source rate; Source rate; Huffman code; Models of communication channels; Error-control codes in transmission systems; Classification of decoding algorithms; Information, energy and frequency efficiency; Research Subject Categories::TECHNOLOGY